Species Difference in the Contribution of T-Type Calcium Current to Cardiac Pacemaking as Revealed by R(−)-Efonidipine - Hikaru Tanaka; Chisa Komikado; Iyuki Namekata; Hideki Nakamura; Mariko Suzuki; Yayoi Tsuneoka; Koki Shigenobu; Akira Takahara (Elsevier, 2008)
The contribution of the T-type Ca2+ current to cardiac pacemaking was examined in isolated right atrial tissue from the mouse, guinea pig, and rabbit using a specific blocker, R(−)-efonidipine. At 10−6 M, R(-)-efonidipine produced negative chronotropy, which was prominent in the mouse and small but significant in the guinea pig. No effect was observed in the rabbit. Microelectrode recordings revealed that R(-)-efonidipine significantly prolongs the pacemaker (phase 4) depolarization of the sinoatrial-node action potential in the mouse and guinea pig. These results provide the first pharmacological evidence that the contribution of T-type Ca2+ current to cardiac pacemaking differs among experimental animal species. Keywords:: R(-)-efonidipine, T-type Ca2+ current, cardiac pacemaking